Study on die shoulder patterning method (DSPM) onto minimizing springback of u-ending - Nurul Jannah, Baharuddin (2022)
U-bending is one of the press-forming processes that has been widely used in the currentmanufacturing industry that involves sheet metal products. Springback phenomenonalways tends to occur in the forming process. After being produced, the bent componenttends to 'move' back to its original shape, which is known as springback. This affects thedimensional accuracy of the formed part. Much research has been done to investigate theparameters that help in minimizing the springback effect on the formed part. However,there is less research on friction provided directly by the Die Shoulder Patterning Method(DSPM) at the corner die shoulder to produce the minimize springback of hat-shapedparts. The actual performance of DSPM in springback behavior remains unclear. Hence,the research attempts to investigate the impact of four DSPM to the springback behavior.The press holding time, Pt (s) of blank and the blank width, w (mm) in the springbackeffect is studied too. The research also covers the interaction between DSPM, blank widthand press holding time in the springback effect. By utilizing these parameters, thelaboratory experiment is conducted, and their effects in springback behavior have beeninvestigated. It is found out that P2’s DSPM with 2 mm pitch size and 1.5 mm pitchdistance tends to have a smaller springback amount on the formed part. Moreover, alonger press holding time of blank helps in reducing the springback effect. Then, P2's hasmore pre-strain growth to deform with the help of longer press holding time to distributethe material flow uniformly. It is also found out that there is no interaction betweenDSPM and press holding time to the springback effects. Based on ANOVA, thehypothesis of interaction between DSPM and blank width to the springback effects wasrejected as it has minor impact on the experiments value.